Tuber aestivum association with non-host roots - Gryndler, Milan; Cerná, Lucie; Bukovská, Petra; Hršelová, Hana; Jansa, Jan (Mycorrhiza, 2014)
Mycorrhizal fungi provide direct and functional interconnection of soil environment with their host plant roots. Colonization of non-host plants have occasionally been described, but its intensity and functional significance in complex plant communities remain generally unknown. Here, the abundance of ectomycorrhizal fungus Tuber aestivum was measured in the roots of host and non-host (non-ectomycorrhizal) plants in a naturally occurring T. aestivum colony using a quantitative PCR approach. The roots of non-host plant species found inside the brûlé area were extensively colonized by T. aestivum mycelium, although the levels were significantly lower than those found in host Carpinus betulus roots. However, fungal biomass concentration in the non-host roots was one to two orders of magnitude higher than that in the surrounding soil. This indicates existence of an important biotic interaction between T. aestivum mycelium and the non-host, mostly herbaceous plants. Roots, either host or non-host, thus probably constitute hot spots of T. aestivum activity in the soil ecosystem with as yet uncovered functional significance.
Keywords: rostliny; mykorhiza; Plants; Mycorrhizae; Plant Roots; kořeny rostlin; Betulaceae; břízovité